Effectiveness of alcohol brief intervention delivered by community pharmacists: study protocol of a two-arm randomised controlled trial - Dhital, Ranjita (BioMed Central, 2013)
BACKGROUND: There is strong evidence to support the effectiveness of Brief Intervention (BI) in reducing alcohol consumption in primary healthcare. METHODS AND DESIGN: This study is a two-arm randomised controlled trial to determine the effectiveness of BI delivered by community pharmacists in their pharmacies. Eligible and consenting participants (aged 18 years or older) will be randomised in equal numbers to either a BI delivered by 17 community pharmacists or a non-intervention control condition. The intervention will be a brief motivational discussion to support a reduction in alcohol consumption and will take approximately 10 minutes to deliver. Participants randomised to the control arm will be given an alcohol information leaflet with no opportunity for discussion. Study pharmacists will be volunteers who respond to an invitation to participate, sent to all community pharmacists in the London borough of Hammersmith and Fulham. Participating pharmacists will receive 7 hours training on trial procedures and the delivery of BI. Pharmacy support staff will also receive training (4 hours) on how to approach and inform pharmacy customers about the study, with formal trial recruitment undertaken by the pharmacist in a consultation room. At three month follow up, alcohol consumption and related problems will be assessed with the Alcohol Use Disorders Identification Test (AUDIT) administered by telephone. DISCUSSION: The UK Department of Health’s stated aim is to involve community pharmacists in the delivery of BI to reduce alcohol harms. This will be the first RCT study to assess the effectiveness of BI delivered by community pharmacists. Given this policy context, it is pragmatic in design. TRIAL REGISTRATION: Current Controlled Trials ISRCTN95216873